Raising quality vegetable seedlings under controlled environment conditions - DINESH PAPPAN D; SANDRA S; SUMA M; VISHAL VIKRAMAN; Er. Anu Varughese (Guide) (Tavanur 2009 KElappaji College of Agricultural Engineering and Technology)
to evaluate the suitability of different protected structures for nursery raising of solanaceous vegetables under different treatments and to compare its performance with that of the open field conditions
Raising quality vegetable seedlings under controlled environment conditions